It’s the End of the Work as We Know It: End of the Work, Complete Automation, Robotic Anarcommunism - Pierpaolo Marrone (Humana.Mente: Journal of Philosophical Studies, 2020)
In this article I explore some consequences of the relations between technique, capitalism and radical liberation ideologies (such as communism and anarcho-communism). My thesis is that the latter are going to rise to the extent that wage labor will become a scarce commodity. Through total automation, however, what may occur will not be the end of the reign of scarcity, but a new oppressive order.